McAlpine's Newfoundland directory, 1898 (McAlpine Directory Co., 1898)
McAlpine's Newfoundland directory lists the inhabitants of the island's various communities with occupation. It also includes general social, economic and governmental information. Includes index to advertisers. Alternative title from common name. Includes advertisements.